Quality of recovery scores in deep serratus anterior plane block vs. sham block in ambulatory breast cancer surgery: a randomised controlled trial. (25th January 2021) - Abdallah, F. W.; Patel, V.; Madjdpour, C.; Cil, T.; Brull, R.
Summary: Deep serratus anterior plane block has been widely adopted as an analgesic adjunct for patients undergoing breast surgery, but robust supporting evidence of efficacy is lacking. We randomly allocated 40 patients undergoing simple or partial mastectomy with sentinel node biopsy to receive either a pre‐operative deep serratus anterior plane block (serratus group) or a placebo injection (sham group), in addition to systemic analgesia. The primary outcome measure was the quality of recovery score at discharge, as assessed by the quality of recovery‐15 questionnaire at various time‐points. Secondary analgesic outcomes included: pain severity; postoperative opioid consumption; opioid‐related side‐effects; patient satisfaction up to 7 days postoperatively; and persistent postoperative pain up to 3 months after surgery. All patients who were recruited completed the study. There were no differences in the quality of recovery‐15 scores between patients in the serratus and control groups, with mean (SD) scores of 96 (14) and 102 (20) for the control and serratus groups, respectively. We were also unable to detect differences in any of the secondary analgesic outcomes examined. The addition of a deep serratus anterior plane block to systemic analgesia does not enhance quality of recovery in patients undergoing ambulatory breast cancer surgery.